2021
DOI: 10.1038/s41398-021-01598-y
|View full text |Cite
|
Sign up to set email alerts
|

Individuals at increased risk for development of bipolar disorder display structural alterations similar to people with manifest disease

Abstract: In psychiatry, there has been a growing focus on identifying at-risk populations. For schizophrenia, these efforts have led to the development of early recognition and intervention measures. Despite a similar disease burden, the populations at risk of bipolar disorder have not been sufficiently characterized. Within the BipoLife consortium, we used magnetic resonance imaging (MRI) data from a multicenter study to assess structural gray matter alterations in N = 263 help-seeking individuals from seven study sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…20.3% of the participants screened positive on one of these syndromes. Surprisingly, SVM could not detect participants at risk estimated using EPIbipolar, although we detected signi cant differences in cortical thickness between the high-risk and no-risk individuals in our previous study [43]. Given similar sample size (previous study N = 263), we pooled the individuals in the high-risk and low-risk groups in order to allow for a binary classi cation.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…20.3% of the participants screened positive on one of these syndromes. Surprisingly, SVM could not detect participants at risk estimated using EPIbipolar, although we detected signi cant differences in cortical thickness between the high-risk and no-risk individuals in our previous study [43]. Given similar sample size (previous study N = 263), we pooled the individuals in the high-risk and low-risk groups in order to allow for a binary classi cation.…”
Section: Discussionmentioning
confidence: 89%
“…However, after removing the low risk group, we obtained a balanced accuracy of 60.9 / 55.5% (10-fold / leave-one-site-out). This suggests, that whereas in a hypothesis driven region-of-interest analysis EPIbipolar selected participants displaying signi cantly thinner cortex in the left pars opercularis [43], BPSS-P selected participants displaying widespread structural alterations enabling for more accurate, single subject classi cation using machine learning. Interestingly, in our above mentioned previous study [43], the pars opercularis was not signi cantly thinner in participants scoring positive in BPSS-P, however, the low p-value might have suggested a non-signi cant trend.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, subjects are categorized into four different risk groups: No risk at present, risk status (at least one secondary symptom accompanied by specific changes in sleep and circadian rhythm), high risk status (one primary and at least one secondary symptom, and ultra-high risk (more than one primary symptom). In later analyses, the high risk and ultra-high-risk groups were fused, since the high-risk group contained a disproportionally low number of subjects (3.2%) [36]. Therefore, we used the EPIbipolar version with three risk categories: no risk, low-risk and high-risk across this manuscript.…”
Section: Risk Assessment Instrumentsmentioning
confidence: 99%
“…For the left IFG, although volume increase is not consistently observed, reduced cortical thickness has been widely reported. A multicenter study found thinner pars opercularis of the left IFG in high-risk participants compared to low-risk participants (Mikolas et al ., 2021 ). Roberts et al .…”
Section: Introductionmentioning
confidence: 99%